2010
DOI: 10.1007/s10592-010-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Levels of connectivity between longnose skate (Dipturus oxyrinchus) in the Mediterranean Sea and the north-eastern Atlantic Ocean

Abstract: Sequencing of a partial region of the mitochondrial control region has revealed no shared haplotypes between longnose skate (Dipturus oxyrinchus L.) sampled in the north-eastern Atlantic (Norway and Rockall) and those sampled in the Mediterranean (Mallorca). Bayesian estimation of the migration rate suggests little, if any, gene flow occurs between the regions and that the populations separated 20,000 years ago. These conclusions provide a genetic basis for long-standing observations, based on egg capsule and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…In the small-spotted catshark, the lack of significant genetic differentiation between the Atlantic and the western Mediterranean at the mtDNA level contrasts the strong genetic differentiation that was detected in the longnose skate (Griffiths et al, 2011a). Griffiths et al (2011a) found no shared haplotypes between the Atlantic and the Mediterranean collections, possibly because the Atlantic collections (Rockall Bank and off Norway) were geographically very distant from the Mediterranean ones (Mallorca and Menorca).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In the small-spotted catshark, the lack of significant genetic differentiation between the Atlantic and the western Mediterranean at the mtDNA level contrasts the strong genetic differentiation that was detected in the longnose skate (Griffiths et al, 2011a). Griffiths et al (2011a) found no shared haplotypes between the Atlantic and the Mediterranean collections, possibly because the Atlantic collections (Rockall Bank and off Norway) were geographically very distant from the Mediterranean ones (Mallorca and Menorca).…”
Section: Discussionmentioning
confidence: 77%
“…Griffiths et al (2011a) found no shared haplotypes between the Atlantic and the Mediterranean collections, possibly because the Atlantic collections (Rockall Bank and off Norway) were geographically very distant from the Mediterranean ones (Mallorca and Menorca). However, the genetic differentiation of both species between the Atlantic and the Mediterranean remains to be clarified with more markers (for example, nuclear) and a more appropriate sampling scheme.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Geographical genetic breaks need to be accurately accounted for when delineating management and conservation units. Behavioural ecology and life-history traits of demersal and bathydemersal skates and rays [103–105] make this group particularly prone to genetic structuring and several cases have already been documented for the region [73,106,107]. Other studies used different mtDNA markers such as parts of the control region or cytochrome b (see for R .…”
Section: Discussionmentioning
confidence: 99%